Altered Grooming Syntax and Amphetamine-Induced Dopamine Release in EAAT3 Overexpressing Mice - Escobar, Angélica P.; Martínez-Pinto, Jonathan; Silva-Olivares, Francisco; Sotomayor-Zárate, Ramón; Moya, Pablo R. (Frontiers in Cellular Neuroscience, 2021)
The excitatory amino acid transporter EAAT3 plays an important role in the neuronal uptake of glutamate regulating the activation of glutamate receptors. Polymorphisms in the gene encoding EAAT3 have been associated with Obsessive-Compulsive Disorder (OCD), although the mechanisms underlying this relationship are still unknown. We recently reported that mice with increased EAAT3 expression in forebrain neurons (EAAT3glo/CMKII) display behavioral and synaptic features relevant to OCD, including increased grooming, higher anxiety-like behavior and altered cortico-striatal synaptic function. The dopamine neurotransmitter system is implicated ritualistic behaviors. Indeed, dopaminergic neurons express EAAT3, and mice lacking EAAT3 exhibit decreased dopamine release and decreased expression of the dopamine D1 receptor. Moreover, EAAT3 plays a role on the effect of the psychostimulant amphetamine. As such, we sought to determine if the OCD-like behavior in EAAT3glo/CMKII mice is accompanied by altered nigro-striatal dopaminergic transmission. The aim of this study was to analyze dopamine transmission both in basal conditions and after an acute challenge of amphetamine, using behavioral, neurochemical, molecular and cellular approaches. We found that in basal conditions, EAAT3glo/CMKII mice performed more grooming events and that they remained in phase 1 of the grooming chain syntax compared to control littermates. Administration of amphetamine increased the number of grooming events in control mice, while EAAT3glo/CMKII mice remain unaffected. Interestingly, the grooming syntax of amphetamine-control mice resembled that of EAAT3glo/CMKII mice in basal conditions. Using in vivo microdialysis, we found decreased basal dopamine levels in EAAT3glo/CMKII compared to control mice. Unexpectedly, we found that after acute amphetamine, EAAT3glo/CMKII mice had a higher release of dopamine compared to that of control mice, suggesting that EAAT3 overexpression leads to increased dopamine releasability. To determine postsynaptic effect of EAAT3 overexpression over dopamine transmission, we performed western-blot analysis of dopaminergic proteins and found that EAAT3glo/CMKII mice have higher expression of D2 receptors, suggesting a higher inhibition of the indirect striatal pathway. Together the data indicate that EAAT3 overexpression impacts on dopamine transmission, making dopamine neurons more sensitive to the effect of amphetamine and leading to a disbalance between the direct and indirect striatal pathways that favors the performance of repetitive behaviors.